National Consensus for the Management of Acute Gastroenteritis in Jordanian Children: Consensus Recommendations Endorsed by the Jordanian Paediatric Society - Mohammed Rawashdeh; Basim Al-Zoubi; Maha Barbar Aliwat; Salma Burayzat; Esam Alhindawi; Ali Attia Al-Matti; Eyad Altamimi (International Journal of Pediatrics)
Diarrhoeal diseases are one of the leading worldwide preventable causes of death among children under 5 years of age. Almost half of children do not receive optimal acute gastroenteritis (AGE) treatment in Jordan. With neither regional nor local guidelines available for AGE, consensus recommendations on the management of paediatric AGE in Jordan were developed by a panel of senior paediatricians and paediatric gastroenterologists and are endorsed by the Jordanian Paediatric Society. Recommendations are based on international guidelines and available relevant literature in relation to the AGE landscape and the healthcare system in Jordan. The prevention of diarrhoeal diseases should focus on the improvement of nutrition, hygiene, and sanitation, the introduction of routine vaccination against rotavirus, and the adoption of a standardised approach for AGE management (oral rehydration solution (ORS) use±adjunct therapies, continued feeding, and avoiding routine antibiotic use). Ondansetron, diosmectite, racecadotril, probiotics, and zinc can be considered adjunct to ORS, if needed. Local data gaps should be addressed. The clinical algorithm for the management of paediatric AGE could promote adherence to practice recommendations and by extension improve health outcomes in children.